Robotically-Assisted Coronary Artery Bypass Grafting. (18th March 2010) - Folliguet, Thierry A.; Dibie, Alain; Philippe, François; Larrazet, Fabrice; Slama, Michel S.; Laborde, François
Abstract : Objectives . Robotic surgery enables to perform coronary surgery totally endoscopically. This report describes our experience using the da Vinci system for coronary artery bypass surgery. Methods . Patients requiring single-or-double vessel revascularization were eligible. The procedure was performed without cardiopulmonary bypass on a beating heart. Results . From April 2004 to May 2008, fifty-six patients were enrolled in the study. Twenty-four patients underwent robotic harvesting of the mammary conduit followed by minimal invasive direct coronary artery bypass (MIDCAB), and twenty-three patients had a totally endoscopic coronary artery bypass (TECAB) grafting. Nine patients (16%) were converted to open techniques. The mean total operating time for TECAB was 372 ± 104 minutes and for MIDCAB was 220 ± 69 minutes. Followup was complete for all patients up to one year. There was one hospital death following MIDCAB and two deaths at follow up. Forty-eight patients had an angiogram or CT scan revealing occlusion or anastomotic stenoses (>50%) in 6 patients. Overall permeability was 92%. Conclusions . Robotic surgery can be performed with promising results.